Simple methods to fabricate Bioglass (R)-derived glass-ceramic scaffolds exhibiting porosity gradient - Bretcanu, Oana; Samaille, Claire; Boccaccini, Aldo R. (Journal of Materials Science, 2008)
The present paper discusses different processing technologies for fabrication of novel 45S5 Bioglass®-derived glass-ceramic scaffolds with tailored porosity gradient for potential application in bone tissue engineering. Different types of scaffolds with continuous or stepwise gradient of porosity were produced by the foam replication technique, using preformed polyurethane (PU) foams as sacrificial templates. After preforming the PU foams in metallic moulds, they were dipped in a 45S5 Bioglass ®-based slurry and subsequently heat treated in a chamber furnace up to 1100 °C. During heating, the organic phase is burned out and the glass sinters and partially crystallises. By using this new approach, Bioglass®-derived glass-ceramic scaffolds with different shapes and porosity profiles were designed. Scanning electron microscopy (SEM) showed that all samples have highly interconnected porous structure, with specific porosity gradients. By modifying the shape and dimensions of the metallic mould, bioactive glass-ceramic scaffolds with complex shapes and different degrees of porosity gradient could be obtained. © 2008 Springer Science+Business Media, LLC.
UnivIS-Import:2015-03-09:Pub.2008.tech.IW.LM.simple